Peranan Satuan Polisi Pamong Praja Dalam Penertiban Reklame Di Kabupaten Deli Serdang - Bima, Bima; Ritonga, Syafruddin; Batubara, Beby Masitho (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The purpose of this research is to find out how its role is civil service police unit policing addresse in district Deli Serdang With effort and impeding factors. The methods used by researchers are qualitative research methods through observation, interviews, and documentation. Research shows that the role civil service police unit in district Deli Serdang judging from the action and according to standard operational procedures the procedure can be done well including punctuality, facility and personnel. Inhibiting factors include the insufficient number of Satpol PP personnel, human resources doesnâ€™t have appropriateÂ  skill, storage facilities, , and the lack of regulations as a legal law.